STUDY OF COGNITIVE IMPAIRMENTS IN PATIENTS WITH MULTIPLE SCLEROSIS - Abdullaeva Muslima Akhatovna; Urokova Vazira Khamidovna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT:As a result of demyelination of nerve fibers in multiple sclerosis, significant disturbances can occur not only in motor functions but also in cognitive functions. This article examines the higher mental functions in patients through a series of tests compared with healthy individuals.